授課教師知覺服務學習課程的核心學習內涵及其檢核機制 Teachers' Perception of the Core Contents and Evaluation Methods of Service Learning Course - 林梅琴 Mei-Chin Lin; 趙珮晴 Pei-Ching Chao; 楊百川 Bai-Chuan Yang; 周宗穎 Zong-Ying Zhou (National Changhua University of Education, 2016)
服務學習在教育改革中漸形一股潮流，臺灣教育部也訂定相關辦法與方案，鼓勵相關單位開設相關課程與活動。為求教師可以評估自己的服務學習課程成效，將從服務學習相關文獻確立核心學習內涵，再歸納檢核方法。本文以自編問卷調查詢問大專院校有帶領 服務學習活動或課程的教師，發現教師認為服務學習的公民意識與素養執行不易，且服務學習的概念尚待釐清；而且教師在服務學習的「認知」和「行為」有差距，凸顯結構化與機制化的重要。最後，針對不同服務學習核心學習內涵，教師有建議和實際採用的 檢核機制，而教師較建議者，實際採用程度也會比較頻繁。據此，未來或許可以有具體有效的服務學習操作手冊或藍圖，增加教師信心與採用頻繁度，也讓學生從中獲益。 Service learning has become a popular trend in current educational reform, and to maintain the pace, the Taiwan Ministry of Education has adopted various strategies and plans in promoting service learning courses and activities within schools. In order to help teachers evaluate the effects of their service learning classes, the author reviewed service learning literature in order to establish its core learning contents and evaluation methods. A survey questionnaire was also used to collect relevant data from teachers. Findings of the study indicate that teachers perceived that the civic consciousness and literacy of service learning are difficult to develop, and that the concept of service learning must be clarified. In addition, there are discrepancies between teachers' "knowledge" and "practice" of service learning, suggesting the need for a basic framework and system for service learning. Finally, regarding the different core contents of service learning, it is noticed that teachers suggested and adopted a number of evaluation methods, with the more often suggested methods being adopted more often in practice. All in all, for the benefit of the students, this study recommends the development of a concrete and effective service learning manual or blueprint, in order to strengthen teachers' confidence and adoption frequency.